Exploring the Potentiality of Producing Sustainable Gum Arabic: Case of Sheikan Locality, North Kordofan State, Sudan - Zeinab Mohamed Hammad; Hassan Elnour Adam; Ibrahim Elnour Ibrahim; Salih Omer Tutu; Hatim Mohamed Ahmed Elamin; Faisal Ismail Musa (Journal of Sylva Indonesiana, 2025)
Gum Arabic is a critical source of livelihood in rural areas of Sudan and a key economic commodity. This study investigates the potential for sustainable gum Arabic production in Sheikan locality, North Kordofan, Sudan. Using participatory Rural Appraisal (PRA), structured questionnaires with 302 households, and focus group discussions, the research assesses household participation, gum resource potential, and production challenges. Results indicate that 93% of the respondents own gum gardens with gum contributes 38% to household income. Additionally, from targeted respondents 37% of the respondents have less than 10 years experiences in gum Arabic activities. Based on respondents’ perception the average gum production of tree/season was (2.79 kg). However, limited participation by youth, inadequate infrastructure, and environmental constrains hinder gum production sustainability. The study recommends that integrating indigenous knowledge with modern practices, expanding youth involvement, and enhancing policy support to secure a sustainable supply of gum Arabic